Graphene / nano-copper composite antibacterial agent, antibacterial polycarbonate and preparation method thereof
The graphene/nanocopper oxide composite antibacterial agent generated through two hydrothermal reactions solves the problem of traditional insolid bonding, significantly improves the antibacterial properties of polycarbonate materials, and achieves better antibacterial effects.
Patent Information
- Application Number
- CN202211667433.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-24
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-24
AI Technical Summary
Traditional graphene is not firmly bound to inorganic metal antibacterial particles and is prone to fall off, affecting the antibacterial properties of polycarbonate materials.
Graphene oxide and nano-copper oxide are used to form a composite antibacterial agent through two hydrothermal reactions. The alkaline copper carbonate and copper citrate are used as copper sources to generate nano-copper oxide with a spindle-shaped structure, which enhances the binding strength with graphene.
Graphene is firmly combined with nano-copper oxide, avoiding agglomeration, significantly improving the antibacterial effect, and providing more lasting antibacterial properties.
Smart Images

Figure CN116041927B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of antibacterial materials, and in particular to a graphene / nano copper oxide composite antibacterial agent, antibacterial polycarbonate and a preparation method thereof. Background Art
[0002] Polycarbonate (PC) is a thermoplastic polymer containing carbonate groups in the molecular chain. It is the fastest growing general-purpose engineering plastic among the five major engineering plastics. With its excellent properties, polycarbonate is widely used in aerospace, automotive industry, electronic appliances, medical equipment, infant toys and packaging materials, and plays an important role in daily life and production. However, in related fields that come into contact with human skin, since polycarbonate materials themselves do not have antibacterial properties, it is easy to spread bacteria and viruses during use, causing harm to human health.
[0003] Adding antimicrobial agents during the polycarbonate molding process can give the material antimicrobial properties. Antimicrobial agents can be divided into inorganic antimicrobial agents, organic antimicrobial agents and natural antimicrobial agents. Organic antimicrobial agents and natural antimicrobial agents are rarely used in the plastic processing industry due to their poor heat resistance, short service life and difficult processing. Inorganic antimicrobial agents have the advantages of safety, durability, heat resistance and simple preparation process, and are ideal additives for the preparation of antimicrobial plastics. Commonly used inorganic antimicrobial agents are divided into metal antimicrobial agents (such as Ag, Cu, Zn) and photocatalytic antimicrobial agents (such as TiO2, ZnO, etc.). Metal antimicrobial agents have good performance and are widely used. Metal antimicrobial agents mainly achieve antimicrobial properties by changing cell permeability, reducing dehydrogenase activity and oxidative stress. During processing, they are usually loaded onto porous honeycomb-shaped carriers such as zeolite, activated carbon, and chitosan by physical adsorption and other methods.
[0004] Graphene has a two-dimensional planar structure, and its sharp surface can act as a "nano knife" on bacteria, cutting the cell membrane and destroying the cell structure, thereby killing bacteria. Graphene also has a large specific surface area and can effectively adsorb antibacterial metal particles, providing more opportunities for contact between antibacterial agents and bacteria. Therefore, the combination of graphene and inorganic metal antibacterial particles and their addition to the polycarbonate processing technology as antibacterial agents can synergistically enhance and give polycarbonate excellent antibacterial properties. However, the traditional method of combining graphene and inorganic metal antibacterial particles is that the combination of graphene and inorganic metal antibacterial particles is not strong and easy to fall off. After adding them to polycarbonate, they are prone to agglomeration, affecting the material properties. Summary of the invention
[0005] Based on this, it is necessary to provide a graphene / nano copper oxide composite antibacterial agent, antibacterial polycarbonate and a preparation method thereof, wherein the graphene and nano copper oxide are firmly combined, not easy to fall off, and have a better antibacterial effect.
[0006] In one aspect of the present application, a method for preparing a graphene / nano copper oxide composite antibacterial agent is provided, comprising the following steps:
[0007] mixing graphene oxide, basic copper carbonate, copper citrate, urea, ammonia water and a solvent to obtain a mixed solution;
[0008] The mixed solution is subjected to two hydrothermal reactions. The first hydrothermal reaction is carried out at a temperature of 130°C to 150°C for 2h to 4h, and the second hydrothermal reaction is carried out at a temperature of 210°C to 230°C for 5h to 7h.
[0009] In some embodiments, the molar ratio of basic copper carbonate to copper citrate is (1-3):1.
[0010] In some of the embodiments, the graphene oxide is 2 to 4 parts, the basic copper carbonate is 0.6 to 2 parts, and the copper citrate is 1 to 2 parts by weight.
[0011] In some of the embodiments, the weight percentage of ammonia water is at least 7.5 times that of the copper salt, which is the one with a larger weight percentage between basic copper carbonate and copper citrate.
[0012] In some of the embodiments, the weight percentage of urea is at least 4 times that of the copper salt, which is the larger one of basic copper carbonate and copper citrate, by weight percentage.
[0013] In some of the embodiments, the oxygen content of graphene oxide is 5% to 10%.
[0014] In some embodiments, the specific surface area of graphene oxide is 150 m 2 / g to 600m 2 / g.
[0015] In another aspect of the present application, a graphene / nano copper oxide composite antibacterial agent prepared by the preparation method is provided.
[0016] In another aspect of the present application, an antibacterial polycarbonate is provided, comprising the graphene / nano copper oxide composite antibacterial agent.
[0017] In another aspect of the present application, a method for preparing an antibacterial polycarbonate is further provided, comprising the following steps:
[0018] Mixing water, ethanol, a dispersant, a coupling agent, a thickener, a binder and an antibacterial agent, wherein the antibacterial agent is the graphene / nano copper oxide composite antibacterial agent;
[0019] The polycarbonate was added to the mixture and mixed again.
[0020] Compared with the prior art, this application has at least the following beneficial effects:
[0021] The preparation method of the graphene / nano copper oxide composite antibacterial agent provided by the present application, using basic copper carbonate and copper citrate as copper sources, and obtaining nano copper oxide by two hydrothermal reactions. In the first hydrothermal reaction, groups such as -OH, -COOH and -NH2 appear after the reaction of citrate in copper citrate, and these groups produce branches with oxygen-containing functional groups on the surface of graphene oxide, and dehydrate and condense to produce an anchoring effect, which can improve the uniform distribution of copper oxide and the bonding strength with graphene oxide. In the second hydrothermal reaction, basic copper carbonate begins to decompose, and the generated copper oxide grows around the first hydrothermal reaction product as the core, thereby obtaining a nano copper oxide with a spindle-shaped (also known as a leaf-shaped) structure, which can have more contact area with the two-dimensional planar structure of graphene oxide, further strengthening the firmness of the combination of graphene and nano copper oxide. Therefore, the graphene / nano-copper oxide composite antibacterial agent obtained by the preparation method of the graphene / nano-copper oxide composite antibacterial agent provided in the present application has very strong bonding between graphene and nano-copper oxide, which is not easy to fall off. When it is added to the matrix, it is not easy to agglomerate, and can play a better antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 This is a scanning electron microscope image of the antibacterial agent prepared in Example 1;
[0024] Figure 2 This is a scanning electron microscope image of the antibacterial agent prepared in Comparative Example 1;
[0025] Figure 3 This is a scanning electron microscope image of the antibacterial agent prepared in Comparative Example 2;
[0026] Figure 4 This is a scanning electron microscope image of the antibacterial agent prepared in Comparative Example 3;
[0027] Figure 5 This is a scanning electron microscope image of the antibacterial polycarbonate prepared in Example 1;
[0028] Figure 6 This is a scanning electron microscope image of the antibacterial polycarbonate prepared in Comparative Example 1;
[0029] Figure 7 This is a scanning electron microscope image of the antibacterial polycarbonate prepared in Comparative Example 2;
[0030] Figure 8 This is a scanning electron microscope image of the antibacterial polycarbonate prepared in Comparative Example 3. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0033] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0034] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 0.3-0.5m / s means that the units of the left endpoint "0.3" and the right endpoint "0.5" are both m / s (meters per second).
[0036] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0037] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0038] The term "graphene / nano-copper oxide" refers to a graphene composite material loaded with nano-copper oxide.
[0039] In one aspect, the present application provides a method for preparing a graphene / nano copper oxide composite antibacterial agent, comprising the following steps:
[0040] (a) mixing graphene oxide, basic copper carbonate, copper citrate, urea, ammonia water and a solvent to obtain a mixed solution;
[0041] (b) subjecting the mixed solution to two hydrothermal reactions, wherein the first hydrothermal reaction is carried out at a temperature of 130°C to 150°C for 2 h to 4 h, and the second hydrothermal reaction is carried out at a temperature of 210°C to 230°C for 5 h to 7 h.
[0042] The oxygen content of graphene oxide may be any value between 5% and 10%, for example, 6%, 7%, 8%, or 9%.
[0043] The sheet diameter of graphene oxide may be any value between 3 μm and 7 μm, for example, 4 μm, 5 μm, or 6 μm.
[0044] The specific surface area of graphene oxide can be 150m 2 / g to 600m 2 / g, for example, it can also be 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g.
[0045] In some embodiments, the molar ratio of basic copper carbonate to copper citrate is any ratio between (1-3): 1, for example, including but not limited to 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1. The molar ratio of basic copper carbonate to copper citrate within this range can obtain a more favorable nano copper oxide morphology structure.
[0046] In some embodiments, by weight, graphene oxide is 2 to 4 parts, basic copper carbonate is 0.6 to 2 parts, and copper citrate is 1 to 2 parts. Within this weight ratio range, a better loading amount can be obtained while avoiding the waste of raw materials.
[0047] In some embodiments, by weight, the weight of ammonia is at least 7.5 times that of copper salt, and the copper salt is one of more weight parts in basic copper carbonate and copper citrate. Understandably, if basic copper carbonate is 0.6 weight part and copper citrate is 1 weight part, the weight of ammonia is at least 7.5 times that of copper citrate, i.e. at least 7.5 weight parts. If basic copper carbonate is 1.5 weight parts and copper citrate is 1 weight part, the weight of ammonia is at least 7.5 times that of basic copper carbonate, i.e. at least 11.25 weight parts. Ammonia plays the role of dissolving copper citrate and basic copper carbonate, and can also provide ammonium ions to participate in hydrothermal reaction.
[0048] In some embodiments, by weight, the weight of urea is at least 4 times that of copper salt, and the copper salt is one of basic copper carbonate and copper citrate with more weight. Understandably, if basic copper carbonate is 0.6 weight parts and copper citrate is 1 weight part, the weight of urea is at least 4 times that of copper citrate, i.e., at least 4 weight parts. If basic copper carbonate is 1.5 weight parts and copper citrate is 1 weight part, the weight of ammonia is at least 4 times that of basic copper carbonate, i.e., at least 6 weight parts. Urea pyrolysis produces CO2 and NH3, which can play an effect of regulating the decomposition rate of basic copper carbonate, and contribute to the size control of the final copper oxide.
[0049] The solvent is usually water, which plays the role of regulating the concentration of copper salt. The concentration of copper salt affects the decomposition rate of reactants and the generation rate of copper oxide to a certain extent. Too high a concentration will cause the reactants to decompose too quickly and the copper oxide to be generated too quickly, which will lead to too fast growth at the same site, and ultimately cause the accumulation and uneven distribution of copper oxide.
[0050] The temperature of the first hydrothermal reaction may be any value between 130°C and 150°C, and understandably may include but is not limited to 130°C, 135°C, 140°C, 145°C, and 150°C.
[0051] The time of the first hydrothermal reaction may be any value between 2 h and 4 h, which may include but is not limited to 2 h, 2.5 h, 3 h, 3.5 h, and 4 h.
[0052] The temperature of the second hydrothermal reaction may be any value between 210°C and 230°C, and understandably may include but is not limited to 210°C, 215°C, 220°C, 225°C, and 230°C.
[0053] The time of the second hydrothermal reaction may be any value between 5 h and 7 h, which may include but is not limited to 5 h, 5.5 h, 6 h, 6.5 h, and 7 h.
[0054] In the first hydrothermal reaction: urea begins to decompose and generate ammonia. When the temperature reaches the critical point, ammonia water and copper citrate begin to partially react to generate copper hydroxide (which decomposes into copper oxide in the second hydrothermal reaction). At the same time, -OH, -COOH and -NH2 groups appear in the citrate after the reaction. These groups branch with the oxygen-containing functional groups on the surface of graphene oxide and dehydrate and condense to produce an anchoring effect, which helps to improve the uniform distribution of copper oxide and the bonding strength with graphene oxide.
[0055] In the second hydrothermal reaction, basic copper carbonate begins to decompose. Since urea pyrolysis produces CO2 and NH3, it can regulate the decomposition rate of basic copper carbonate and help control the size of the final copper oxide. As basic copper carbonate decomposes, the copper oxide produced grows into spindle-shaped (or leaf-shaped) nano-copper oxide around the copper oxide generated by the copper citrate reaction as the core.
[0056] In some embodiments, the method for preparing the graphene / nano copper oxide composite antibacterial agent further comprises:
[0057] (c) subjecting the reactants after the second hydrothermal reaction in step (b) to solid-liquid separation;
[0058] (d) washing and drying the solid phase after solid-liquid separation.
[0059] The solid-liquid separation method can be any conventional method known in the art, such as centrifugation, filtration, etc.
[0060] The purpose of cleaning is to remove excess ammonia, urea and other raw materials. Deionized water can be used for cleaning. The standard for judging whether the cleaning is complete is that the pH of the solution after cleaning is neutral.
[0061] The drying method may also be any conventional method known in the art, such as natural drying, air drying, oven drying, vacuum drying, freeze drying, etc.
[0062] In another aspect, the present application provides a graphene / nano copper oxide composite antibacterial agent prepared by the preparation method of any of the above embodiments.
[0063] In another aspect, the present application further provides an antibacterial polycarbonate, which comprises a polycarbonate matrix and the above-mentioned graphene / nano copper oxide composite antibacterial agent.
[0064] The antibacterial polycarbonate can be prepared by any conventional method.
[0065] In another aspect, the present application further provides a method for preparing an antibacterial polycarbonate, comprising the following steps:
[0066] (A) mixing water, ethanol, a dispersant, a coupling agent, a thickener, a binder and the graphene / nano copper oxide composite antibacterial agent;
[0067] (B) Add polycarbonate to the mixture and mix again.
[0068] Water mainly plays a dispersing role, which can blend the dispersant, coupling agent, thickener, binder and antibacterial agent to make them more evenly dispersed.
[0069] Ethanol mainly plays a role in enhancing the compatibility between the organic phase and the inorganic phase.
[0070] The dispersant is not particularly limited and may be any conventional dispersant in the art, for example, including but not limited to succinimide, polyisobutylene amine, polyisobutylene succinimide and any combination thereof.
[0071] The coupling agent is not particularly limited and can be any conventional agent in the art, preferably a silane coupling agent, for example, including but not limited to KH-550, KH-560, KH-570 and any combination thereof. The Chinese name of KH-550 is γ-aminopropyltriethoxysilane, the Chinese name of KH-560 is γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, and the Chinese name of KH-570 is γ-methacryloxypropyltrimethoxysilane.
[0072] The thickener is not particularly limited and can be any conventional agent in the art, for example, it can include but is not limited to polyacrylic acid, polyacrylate, polyurethane, high molecular weight polyethylene oxide and any combination thereof, preferably polyacrylic acid. The amount of thickener used is conventional,
[0073] The binder also acts as a stabilizer and may be selected from hydroxypropyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and any combination thereof.
[0074] The amounts of water, ethanol, dispersant, coupling agent, thickener and binder are all conventional amounts.
[0075] The dosage of the graphene / nano copper oxide composite antibacterial agent is 1 / 4 to 1 / 3 of the weight of the polycarbonate.
[0076] The mixing method in step (A) and step (B) can be conventional mixing, such as mechanical stirring.
[0077] The following are specific embodiments. The purpose is to further explain the present application in detail to help the technical personnel and researchers in the field to further understand the present application. The relevant technical conditions do not constitute any limitation to the present application. Any form of modification made within the scope of the claims of the present application is within the scope of protection of the claims of the present application.
[0078] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available or can be prepared by known methods. The instruments are all conventionally selected in the art. The experimental methods without specific conditions in the examples are carried out according to conventional conditions, such as the conditions described in the literature, books or the methods recommended by the manufacturer.
[0079] Example 1
[0080] 1. Add 3 parts by weight of graphene oxide (sheet diameter 3-7 μm, oxygen content 5-10%, prepared by Hummers method), 2 parts by weight of basic copper carbonate, 2 parts of copper citrate, 15 parts of ammonia water, 5 parts of urea and 20 parts of deionized water into a beaker and mix. After stirring at room temperature for 2 hours, transfer it to a hydrothermal reactor containing a polytetrafluoroethylene substrate, first heat it at 130° C. for 3 hours (the first hydrothermal reaction), then heat it at 210° C. for 6 hours (the second hydrothermal reaction), cool it, centrifuge and wash the mixture, remove the supernatant, and vacuum dry it to obtain a graphene composite antibacterial agent loaded with copper oxide.
[0081] 2. Stir 60 parts of deionized water, 20 parts of anhydrous ethanol, 3 parts of dispersant (succinimide), 5 parts of coupling agent (KH-550), 10 parts of graphene composite antibacterial agent loaded with copper oxide, 1 part of polyacrylic acid thickener and 3 parts of hydroxypropyl cellulose, then add 30 parts of polycarbonate, set the speed to 400 rpm, stir for 1 hour, and keep turning the polycarbonate pellets during stirring to ensure that the graphene antibacterial agent is fully attached.
[0082] 3. After the stirring is completed, the polycarbonate pellets are fished out, placed in a vacuum oven, and dried at 120° C. for 6 hours. After drying, the antibacterial polycarbonate is obtained.
[0083] Example 2
[0084] The preparation method is basically the same as that of Example 1, except that the first hydrothermal reaction temperature is 150° C. and the reaction time is 2 h.
[0085] Example 3
[0086] The preparation method is basically the same as that of Example 1, except that the second hydrothermal reaction temperature is 230° C. and the reaction time is 5 h.
[0087] Example 4
[0088] The preparation method is basically the same as that of Example 1, except that the first hydrothermal reaction time is 4 h, and the second hydrothermal reaction time is 7 h.
[0089] Comparative Example 1
[0090] The preparation method is basically the same as that of Example 1, except that the copper salt is only copper citrate.
[0091] Comparative Example 2
[0092] The preparation method is basically the same as that of Example 1, except that the copper salt is only basic copper carbonate.
[0093] Comparative Example 3
[0094] The preparation method is basically the same as that of Example 1, except that the copper salt is only copper sulfate.
[0095] Comparative Example 4
[0096] The antibacterial agent in step 2 of Example 1 was replaced with a copper ion antibacterial agent (particle size 100 nm).
[0097] The morphology test of the antibacterial agents prepared in Examples 1 to 4 and Comparative Examples 1 to 4 and the antibacterial test on the polycarbonate material were performed:
[0098] 1. Morphology test
[0099] like Figure 1 The figure shows a scanning electron microscope image of the antibacterial agent prepared in Example 1. It can be seen from the figure that the nano copper oxide in the antibacterial agent is in the shape of a shuttle (also called a leaf shape), and its distribution in the graphene is uniform and not agglomerated. The nano copper oxide in the antibacterial agents prepared in Examples 2 to 4 are all in the shape of a shuttle.
[0100] like Figures 2 to 4 As shown, it is the scanning electron microscope image of the antibacterial agent prepared in comparative examples 1 to 3. It can be seen from the figure that the nano copper oxide in the antibacterial agent is nearly spherical, rather than spindle-shaped, which is significantly different from the shape of the nano copper oxide in Example 1.
[0101] like Figure 5 , which is a scanning electron microscope image of the polycarbonate prepared in Example 1. It can be seen from the image that the antibacterial agent is evenly distributed in the polycarbonate matrix without agglomeration.
[0102] like Figures 6 to 8Shown are scanning electron microscope images of the polycarbonates prepared in Comparative Examples 1 to 3. It can be seen from the images that the antibacterial agent is very unevenly distributed in the polycarbonate matrix, and large agglomerates appear.
[0103] 2. After the antibacterial polycarbonate is processed into a 5cm*5cm*1mm sheet by injection molding, it is tested according to the GB / T31402-2015 plastic surface antibacterial performance test method. The antibacterial durability is to immerse the sample in deionized water to ensure complete immersion and keep it fully stirred. The antibacterial performance after a certain period of time is tested. Here, the antibacterial performance of 0 days, 90 days and 180 days is tested respectively, and the test bacteria are Escherichia coli, Staphylococcus aureus and Candida albicans.
[0104] The results are shown in Table 1:
[0105] Table 1
[0106]
[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0108] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.
Claims
1. A method for preparing a graphene / nano copper oxide composite antibacterial agent, characterized in that: The following steps are involved: mixing graphene oxide, basic copper carbonate, copper citrate, urea, ammonia water and a solvent to obtain a mixed solution; The mixed solution is subjected to two hydrothermal reactions, the first hydrothermal reaction being at a temperature of 130° C. to 150° C. for 2 h to 4 h, and the second hydrothermal reaction being at a temperature of 210° C. to 230° C. for 5 h to 7 h.
2. The method for preparing the graphene / nano copper oxide composite antibacterial agent according to claim 1, characterized in that: The molar ratio of basic copper carbonate and copper citrate is (1-3):
1.
3. The method for preparing the graphene / nano copper oxide composite antibacterial agent according to claim 1, characterized in that: In terms of weight, the graphene oxide is 2 to 4 parts, the basic copper carbonate is 0.6 to 2 parts, and the copper citrate is 1 to 2 parts.
4. The method for preparing the graphene / nano copper oxide composite antibacterial agent according to claim 1, characterized in that: In terms of weight, the weight of ammonia water is at least 7.5 times that of the copper salt, and the copper salt is the one with a larger weight between basic copper carbonate and copper citrate.
5. The method for preparing the graphene / nano copper oxide composite antibacterial agent according to claim 1, characterized in that: In terms of weight, the weight of urea is at least 4 times that of the copper salt, and the copper salt is the one with a larger weight between basic copper carbonate and copper citrate.
6. The method for preparing the graphene / nano copper oxide composite antibacterial agent according to any one of claims 1 to 5, characterized in that: The oxygen content of graphene oxide is 5% to 10%.
7. The method for preparing the graphene / nano copper oxide composite antibacterial agent according to any one of claims 1 to 5, characterized in that: The specific surface area of graphene oxide is 150m 2 / g to 600m 2 / g.
8. A graphene / nano copper oxide composite antibacterial agent prepared by the preparation method according to any one of claims 1 to 7.
9. An antibacterial polycarbonate, characterized in that: It includes the graphene / nano copper oxide composite antibacterial agent as described in claim 8.
10. A method for preparing an antibacterial polycarbonate, characterized in that: The following steps are involved: Mixing water, ethanol, a dispersant, a coupling agent, a thickener, a binder and an antibacterial agent, wherein the antibacterial agent is the graphene / nano copper oxide composite antibacterial agent according to claim 8; The polycarbonate was added to the mixture and mixed again.
